Effectiveness of the Madrasah Development Team in Enhancing Educational Quality at MTsN 1 East Aceh - Firmansyah, Devi; Arianto, Sofyan; Almuhajir, A (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to analyze the effectiveness of the development team's role in improving the quality of education at MTsN 1 Aceh Timur. Utilizing a qualitative approach with a case study design, this research explores local dynamics and challenges faced during program implementation. The results indicate that the development team significantly contributes to increasing institutional attractiveness, transforming learning processes, and strengthening networks with various stakeholders. Despite managerial challenges such as resource limitations and increased workloads, adaptive strategies and the establishment of a quality assurance team are expected to address these obstacles. This research also highlights the importance of collaboration among managers, educators, and students in creating a conducive environment for quality improvement in education. The novelty of this study lies in its focus on the collective role of the development team within the specific context of madrasahs. Future research is recommended to explore more integrated collaborative models and involve the perspectives of students and parents in program evaluations.